Game technogies in teaching "Mathematical modeling" - Zamyatina O. M. Oksana Mikhailovna; Mozgaleva P. I. Polina Igorevna; Marukhina O. V. Olga Vladimirovna; Goncharuk Yu. O. Yuliya Olegovna (2015, 2015)
Title screen